Physicists research practices: A perspective to rethink inquiry-based science education - El Hage, Suzane (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2021)
Inquiry-Based Science Education (IBSE) is presented as derived from a scientific approach where students are invited to work in the way scientists work.  Studying the proximity between IBSE and scientific approach can be done through different perspectives; the focus here is on the scientific approach. The goal of this case study consists in exploring the ways in which scientists perform their research by interviewing 8 French physicists volunteers to participate in the study. This preliminary research is the first step   to analyze the contemporary physicists’ through research practices, and then to enrich and question IBSE in a different way. The interviews are analyzed in terms of moments, specifically a moment called “to explore/to experiment” with the ck¢ (conception, knowing, concept)framework allowing to model the conceptions of researchers. The results only show two common operators (R) related to the moment “to explore/ to experiment” concerning the research processes of the 8 physicists. However, zero control structures (∑) are common to any of them.